Internet Of Things Water Quality Monitoring System - Chew, Yuin Yee (2020)
In this report, it will be discussing about Internet of Things (IoT) water quality monitoring system. The demand for seafood is increasing with decreasing of wild fish in the ocean. At some point, nature can no longer produce enough seafood for human consumption. Therefore, aquaculture is a tool to fill up the gap for the demand for seafood. Up until today, many aquaculture monitoring systems have yet to be connected to the internet. Farmers needs to be on the site to measure the water parameters which is time and labor-intensive. Since, global demand for seafood is increasing, any potential threat will slow down the production of aqua farming or may cause risk to the consumer’s health. The aim is to develop a real-time water quality monitoring system that is accessible anywhere in the world with the access of internet by utilizing Internet of Things technology. The objectives of this project are design and develop an embedded system architecture to perform real-time water quality monitoring, integrating IoT into real-time water quality monitoring system, and develop an Android GUI to display the water quality in a graphical format. The entire embedded system will be based on Arduino platform and Firebase cloud server to store the data. Arduino Nano was used to logged data from pH sensor, temperature sensors, and turbidity sensor and store it in both SD Card and Firebase cloud server. ESP8266 was used as data transmission gateway to communicate Arduino Nano to Firebase. Moreover, an Android application was developed specifically to allow user to monitor the fish farm from time to time and provide a graphical format to view the historical logged data. In addition, a custom mounting structure and housing was designed to mount all the electronics in the floating platform and power system architecture was also designed to run the entire system on rechargeable battery and solar power. The overall system is working and it is able to log data for 24 hours 7 days at aquaculture farm without without any human assistance. In conclusion, an Internet of Things water quality monitoring system has been successfully designed and developed. This system allows aquaculture farmer to monitor each of the fish ponds in real-time with several features such as real-time data logging, real-time notification and preview historical data in graphical format. Moreover, this system will be able to assist aquaculture farmer to detect water quality problems at the early stage and thus countermeasures can be planned ahead to prevent or reduce aquaculture lost.